The invasive microalga Chrysophaeum taylorii: Interactive stressors regulate cell density and mucilage production. (August 2017) - Caronni, Sarah; Calabretti, Chiara; Cavagna, Gianluca; Ceccherelli, Giulia; Delaria, Maria Anna; Macri, Giovanni; Navone, Augusto; Panzalis, Pieraugusto
Abstract: The benthic mucilage producing microalga Chrysophaeum taylorii Lewis and Bryan ( Pelagophyceae ) has recently received attention for its rapid spread in the Mediterranean Sea, where its blooms have remarkable detrimental effects. So far no information on C. taylorii response to multiple stressors, especially in terms of mucilage hyperproduction, is available in the literature yet, and a manipulative field experiment in this topic was designed in Tavolara Punta Coda Cavallo Marine Protected Area. The aim of the study was to test the effects of nutrient enrichment (addition of nutrients), mechanical disturbance (partial and total benthic organisms removal) and hydrodynamics (increased water turbulence) on C. taylorii cell density and mucilage abundance. To the purpose, the three above mentioned stressors were simulated and the three treatments were assigned to 20 × 20 cm plots following a full-factorial design (n = 3). Interactive effects of the three stressors affected significantly both benthic C. taylorii cell density and mucilage cover although differently. Mechanical disturbance and high hydrodynamics produced consistent effects on cell density and mucilage production (i.e. the former factor enhancing and the latter decreasing). Nutrient enrichment on the contrary led to contrasting effects, promoting cell abundance and inhibiting mucilage production. Therefore, important mucilage blooms are expected in oligotrophic sheltered coastal locations where barren areas are present. Highlights: The interactive effects of different stressors affect the microalga Chrysophaeum taylorii. Nutrient enrichment promotes cell abundance and inhibits mucilage production. Mechanical disturbance enhances its cell density and mucilage production. High hydrodynamics decreases both cell density and mucilage production.